Current State of Overlapping, Concurrent, and Multiple‐Room Surgery in Otolaryngology: A National Survey. (8th August 2017) - Cognetti, David M.; Nussenbaum, Brian; Brenner, Michael J.; Chi, David H.; McCormick, Michael E.; Venkatraman, Giri; Zhan, Tingting; McKinlay, Alex J.
Abstract : Objective: Multiple‐room surgery has gained attention due to reports in the lay press scrutinizing the activity, with hospitals and the government collecting data on current practice. We studied practices and attitudes toward multiple‐room surgery in otolaryngology. Methods: A survey was developed by members of the Patient Safety and Quality Improvement Committee of the American Academy of Otolaryngology—Head and Neck Surgery. The survey was distributed to members of the Academy and included questions on demographics, current practices, and opinions regarding multiple‐room surgery. The survey was designed to capture the spectrum of multidisciplinary, overlapping, and simultaneous/concurrent surgery practices. Data were collected via SurveyMonkey. Results: A total of 907 of 9520 members completed the survey. Of the respondents, 40.4% reported performing some form of multiple‐room surgery. Multiple‐room surgery is more common amongst subspecialists than general otolaryngologists. Most believed that regulations disallowing multiple‐room surgery would result in an increase in late starts (73.5%), an increase in the time to schedule surgery (84.5%), a detriment to residency training (63.1%), and no improvement in patient safety (60%.) Discussion: Multiple‐room surgery is common among responding otolaryngologists. Most respondents consider the practice to serve a role in facilitating access, efficiency, and training. Implications for Practice: Due to recent attention placed on multiple‐room surgery, institutions are reviewing policies regarding the practice. This survey suggests that policy changes that restrict multiple‐room surgery must consider a potential unintended negative impact on patient care and access.